Research handbook on the EU's common foreign and security policy - Blockmans, S. F., 1973-; Koutrakos, Panos (Research handbooks in European law, 2018)
At a critical time for the identity and policy direction of the EU, this Research Handbook examines the dynamics behind the development of the Common Foreign and Security Policy (CFSP) and the Common Security and Defence Policy (CSDP). The Research Handbook includes chapters from renowned experts that examine the efficacy and visibility of the EU as a diplomatic, military and civilian actor in a turbulent world. The authors' original contributions address the impact that existing frameworks, structures and procedures have on the effectiveness of the EU as an international actor and consider the legal challenges to the EU's integrated approach to external action. The Research Handbook on the EU's Common Foreign and Security Policy brings together academics and practitioners from different areas of law (EU and international law) and from the political science field. The interdisciplinary approach makes it essential reading for scholars of law, political science and international relations. Policymakers and all those with an interest in the external activities of the EU will also find this an insightful resource.